Long response duration to pembrolizumab in metastatic, castration-resistant prostate cancer with microsatellite instability-high and neuroendocrine differentiation: A case report - Yoshida, Tsukasa; Yaegashi, Hiroshi; Toriumi, Ren; Kadomoto, Suguru; Iwamoto, Hiroaki; Izumi, Kouji; Kadono, Yoshifumi; Ikeda, Hiroko; Mizokami, Atsushi (Frontiers in Oncology, 2022)
Background: The detection of microsatellite instability in urologic cancers is rare, especially in metastatic, castration-resistant prostate cancer with neuroendocrine differentiation. Case Presentation: This is a case of a 66-year-old Asian male with prostate adenocarcinoma who had metastases at initial presentation. Despite combined androgen deprivation therapy, his prostate-specific antigen (PSA) progressively increased, and prostate re-biopsy revealed small cell carcinoma. He was treated with platinum-based systemic chemotherapy, and his tumor markers, including PSA, remained negative; however, his local symptoms worsened. Subsequently, microsatellite instability-high was detected, and pembrolizumab was administered resulting in complete remission with resolution of symptoms and continued therapeutic effect for more than 14 months. Conclusion: Microsatellite instability testing should be considered, despite its low detection rate, because response to pembrolizumab in metastatic, castration-resistant prostate cancer with detectable microsatellite instability is associated with a prolonged duration of response.